2007
DOI: 10.1038/ncb1642
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine-methyltransferase-dependent oncogenesis

Abstract: Enzymes that mediate reversible epigenetic modifications have not only been recognized as key in regulating gene expression and oncogenesis, but also provide potential targets for molecular therapy. Although the methylation of arginine 3 of histone 4 (H4R3) by protein arginine methyltransferase 1 (PRMT1) is a critical modification for active chromatin and prevention of heterochromatin spread, there has been no direct evidence of any role of PRMTs in cancer. Here, we show that PRMT1 is an essential component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
253
1
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(265 citation statements)
references
References 34 publications
6
253
1
5
Order By: Relevance
“…Functional dissection of protein complexes associated with oncogenic transcription factors, which often represent the initiating events in acute leukemia (24), is critical for understanding the transformation mechanisms and identifying potential therapeutic targets for intervention of self-renewal pathways corrupted in cancer stem cells (20,22,(25)(26)(27). CBF␤, which plays an important role for wild-type AML1 functions, in part by increasing its DNA binding ability (28) and stability (29), has been thought to be a critical component and potential target for AE-mediated transformation (1,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional dissection of protein complexes associated with oncogenic transcription factors, which often represent the initiating events in acute leukemia (24), is critical for understanding the transformation mechanisms and identifying potential therapeutic targets for intervention of self-renewal pathways corrupted in cancer stem cells (20,22,(25)(26)(27). CBF␤, which plays an important role for wild-type AML1 functions, in part by increasing its DNA binding ability (28) and stability (29), has been thought to be a critical component and potential target for AE-mediated transformation (1,10).…”
Section: Discussionmentioning
confidence: 99%
“…RTTA was performed as previously described (20,22,25). In vitro transformation was defined as enhanced self-renewal of primary hematopoietic cells beyond 3 rounds of plating in the serial replating assay.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the cytoplasmatic MLL translocation partner EEN, histone arginine methylation catalyzed by PRMT1 has been shown to be critically important for transformation. 123 It may be that even the molecularly defined group of MLL-rearranged leukemias will undergo further subdivision. An important future goal will be to establish chromatin maps for leukemia propagating (stem) cells.…”
Section: Spotlightmentioning
confidence: 99%
“…Several Trx and PcG genes encode lysine methyltransferases that contain a suppressor of variegation, enhancer of zeste, and Trithorax (SET) domain and target histone proteins to activate or repress transcription, respectively. Genetic alterations of several Trx and PcG genes, including members of the mixed lineage leukemia (MLL) family, have been linked to oncogenesis in mammals and are especially prevalent in hematological malignancies (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Arginine methylation influences protein nuclear localization and intermolecular interactions, thereby affecting various cellular processes, including mRNA splicing and gene transcription. Currently, eight genes have been identified that encode active protein-arginine methyltransferases (PRMTs) in mammals (PRMTs 1,2,3,4,5,6,7, and 8) (24,25). These enzymes mediate mono-and dimethylation of arginine residues and are classified as Type I (PRMTs 1, 2, 3, 4, 6, 7, and 8) or Type II (PRMT 5) enzymes based on their ability to cata-* This work was supported, in whole or in part, by National Institutes of Health Training Grants T32 CA00929930 and T32 CA929931A1 (to J. S.…”
mentioning
confidence: 99%